Internet of Things Enhanced Maritime Robot for Ocean Waste Cleanup - S, Sabarinathan; M, Chandraman; S, Prasanth; IB, Riyaz Ahamed; SV, Praveen; K, Yuvaraj (Journal of Electronics and Informatics, 2024)
Plastic pollution is a major environmental concern, particularly in aquatic habitats. The accumulation of floating debris in water bodies caused by plastic pollution negatively impacts ecosystems, aquatic life, and water quality. The objective of this proposed study is to develop a remote-controlled boat equipped with sensors for measuring water quality and an efficient waste collection system. These sensors provide important information about the environmental conditions of the water body by measuring important factors like pH, dissolved oxygen, and turbidity. The data on water quality helps identify the regions that require immediate attention to prevent and manage pollution, as well as assess the overall health of the ecosystem. The primary goal of the research is to significantly reduce the plastic waste in marine areas, promote sustainable practices, and raise public awareness about the need to address marine pollution, ultimately enhancing a healthier marine ecosystem.
Keywords: Marine pollution; Ocean waste collection; Remote controlled boat; IoT-Data Collection; Water quality monitoring; PH-sensor